State-of-the-Practice in Evaluation of Quality of Experience in Real-Life Environments - Matulin, Marko; Mrvelj, Štefica (Promet - Traffic&Transportation, 2013)
Continuous monitoring of achieved level of service quality in packet-switched networks represents an activity of major importance for network and service providers. This is paramount for network resources provisioning which have to satisfy expectations of fickle customers. However, providing enough resources to specific user does not automatically increase their Quality of Experience (QoE), hence understanding of the relationship between these two is crucial in the network management process. Essentially, this requires subjective testing of service quality which is usually done in controlled environments such as laboratories. Nevertheless, the most accurate subjective evaluation of QoE includes real-life experiments in the environments where the services are actually used. Therefore, the aim of this paper is to provide a review of the current state-of-the-practice in evaluating QoE in real-life environments.